2021
DOI: 10.3389/fendo.2021.636038
|View full text |Cite
|
Sign up to set email alerts
|

New Human Follitropin Preparations: How Glycan Structural Differences May Affect Biochemical and Biological Function and Clinical Effect

Abstract: It is well accepted that pituitary follitropin is secreted into the circulation as a mixture of variants, which differ not in primary structure but rather at the level of glycosylation. These glycosidic forms vary in the number of glycosylation sites filled, complexity of glycosidic chains, and sialylation and sulfation. It is generally agreed that high sialylation, 2,3 sialic acid capping of terminal N-acetyl galactosamine or galactose leads to longer circulating half-life, by blocking binding of asialoglycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 94 publications
(174 reference statements)
1
42
0
Order By: Relevance
“…This hormone is produced in the anterior pituitary and travels through the circulation to gonodal cells where it interacts with FSH receptors (FSHRs) to promote follicle development in women and spermatogenesis in men ( Daya 2004 ; Davis et al, 2014 ; Ulloa-Aguirre et al, 2018 ). Therapeutically, recombinant FSH or follitropins can substitute for naturally-occurring FSH deficiencies to treat infertility ( Dias & Ulloa-Aguirre 2021 ).…”
Section: Impact Of Glycosylation On Pharmacodynamics and Biological A...mentioning
confidence: 99%
See 3 more Smart Citations
“…This hormone is produced in the anterior pituitary and travels through the circulation to gonodal cells where it interacts with FSH receptors (FSHRs) to promote follicle development in women and spermatogenesis in men ( Daya 2004 ; Davis et al, 2014 ; Ulloa-Aguirre et al, 2018 ). Therapeutically, recombinant FSH or follitropins can substitute for naturally-occurring FSH deficiencies to treat infertility ( Dias & Ulloa-Aguirre 2021 ).…”
Section: Impact Of Glycosylation On Pharmacodynamics and Biological A...mentioning
confidence: 99%
“…Endogenous FSH consists of an alpha and beta subunit; both have two putative sites of N-glycosylation. The alpha subunit is consistently fully glycosylated with the beta subunit occupied with zero, one, or two N-glycans ( Davis et al, 2014 ; Ulloa-Aguirre et al, 2018 ; Dias & Ulloa-Aguirre 2021 ). The alpha subunit of FSH plays a pivotal role in receptor interactions by engaging the receptor-ligand interface ( Ulloa-Aguirre et al, 2018 ; Dias & Ulloa-Aguirre 2021 ).…”
Section: Impact Of Glycosylation On Pharmacodynamics and Biological A...mentioning
confidence: 99%
See 2 more Smart Citations
“…FSH is a glycoprotein, and it was recently shown that the hypo-glycosylated forms might be more efficient in promoting follicular growth and supporting granulosa cell survival in vivo , possibly by increasing serum estradiol levels ( 22 ). Interestingly, young women express partially glycosylated FSH whereas postmenopausal women express mainly the fully glycosylated form ( 23 , 24 ), and this might influence both the biochemical properties and the efficacy of the various FSH preparations ( 25 ). This issue has been thoroughly discussed in a Delphi Consensus study recently ( 26 ).…”
Section: Introductionmentioning
confidence: 99%